Development of Bengkulu Traditional Cake Marketing through E-Commerce Media - Ilham Rivaldo Pratama; Leni Natalia Zulita; Herlina Latipa Sari (Penerbit Jurnal Indonesia, 2021)
Ummi shop is a company engaged in the sale of traditional cakes. The sales system used today is a conventional system, where the buyer must come directly to the Garsel Shop to see the products offered. With this system, it will take the consumer's time so that it is difficult to obtain information about the specifications of the product being offered. E-Commerce or in Indonesian, namely electronic commerce is the distribution, purchase, sale, marketing of goods and services through electronic systems such as the internet or television, www, or other computer networks. E-commerce can involve electronic funds transfer, electronic data exchange, automated inventory management systems, and automated data collection systems. At this time, Ummi Store has not used the e-commerce facility so that it is difficult to offer products to consumers who are outside the city. In addition, it can also have an impact that affects the product sales process, namely the ignorance of consumers who are outside the city of the existence of Ummi Shops. The process of selling the Ummi Store will only be carried out if there are consumers who come to the store, while many consumers who are outside the city cannot come or do not know the existence of the Ummi Store. To build this e-commerce system, the tools used to describe the system model are in the form of a data flow diagram (FlowMap), context diagrams, and Data Flow Diagrams (DFD), as well as in database design using a data dictionary and Entity Relationship Diagram (ERD). With the existence of e-commerce is expected to make it easier for consumers to obtain information about product specifications offered by Ummi Stores. Make it easy for Ummi shops to offer or sell their products to consumers who are outside the city. Consumers who are outside the city can find out the existence of Ummi stores by using this e-commerce service and can order without having to come to the store. Make it easy for consumers to process payments because there are several options in the payment process. With a good product data processing or management system that is equipped with security, it will support the performance of the system.